2020
DOI: 10.1177/1465750320903621
|View full text |Cite
|
Sign up to set email alerts
|

How firms risk through entrepreneurial innovations: Behavioural patterns and implications

Abstract: The purpose of this article is to develop a conceptual framework clarifying how firms behaviourally venture or risk through entrepreneurial innovation (EI), in the ‘contexts’ of globalisation, society, innovation users or public perceptions; we methodologically coined these ‘contexts’ as ‘4-GSIP variables’ and applied them in that order. We then examined EI literature and built on variants of its theoretical insights to describe conceptual frameworks of how innovation focus firms behaviourally deal wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…However, our findings reveal that in this current pandemic, Jordanian SMEs have seen proactivity as a means to improvise new organisational practices that disrupted the established organisational routines. We complement the work of Ahworegba et al (2020) ; Asyari (2021) and Kuckertz et al (2020) by employing EO to understand SMEs’ resilience and to develop five entrepreneurial capabilities: efficiency-based capability, adaptive capability, collaborative capability, mastering change and learning capability. We propose that these capabilities reduce the sources of vulnerabilities and shield SMEs with preparedness and adaptation in the face of major disruptions ( Rank and Strenge, 2018 and Freixanet et al, 2020 ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our findings reveal that in this current pandemic, Jordanian SMEs have seen proactivity as a means to improvise new organisational practices that disrupted the established organisational routines. We complement the work of Ahworegba et al (2020) ; Asyari (2021) and Kuckertz et al (2020) by employing EO to understand SMEs’ resilience and to develop five entrepreneurial capabilities: efficiency-based capability, adaptive capability, collaborative capability, mastering change and learning capability. We propose that these capabilities reduce the sources of vulnerabilities and shield SMEs with preparedness and adaptation in the face of major disruptions ( Rank and Strenge, 2018 and Freixanet et al, 2020 ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The accumulation of knowledge and experience about market dynamics and different behaviours throughout the pandemic has turned on an interventionist approach, in which case, SMEs started to innovate solutions and communication channels with their customer base (Abualqumboz et al, 2020). Our findings revealed that most SMEs developed a robust risk management process and adopted diversification strategies that are responsive to shifts in customer preferences, such as transforming the supply chain from end consumers to farthest tier suppliers (Ahworegba et al, 2020;Duchek, 2020). With this in mind, SMEs have also defined a method for assessing the risk associated with each action or strategy or on any channel in the supply chain and with each warehouse, factory, supplier, or mode of transport.…”
Section: How Entrepreneurial Orientation Contributes To Smes' Resilience?mentioning
confidence: 98%
See 1 more Smart Citation
“…The innovation is directly associated with internal knowledge creation, external information sourcing and external collaboration [Stephan et al (2019)] and within the business universe, innovation is fundamental to the economic development of companies [Calik et al (2020)]. In terms of innovation metrics, some studies emphasize aspects such as culture, knowledge, organizational success, strategies, collaboration and the organization itself [Rosa et al (2020)], that constitute the process of developing new products or services for future commercial and social benefits (Ahworegba et al, 2020).…”
Section: Characteristics Authorsmentioning
confidence: 99%
“…Subsequently, Amorós et al (2019Amorós et al ( , p. 1405) defined entrepreneurial innovations as innovative and ambitious entrepreneurial activities in emerging economies that emerge within environments characterized by favorable policy support towards entrepreneurs, government subsidies for new technology, as well as R&D policies. It inspired a few researchers to analyze the phenomenon in other emerging economies (Dossou and Ju 2019; Komlósi et al 2019;Sharma and Sharma 2019;Ahworegba et al 2020). In this chapter, based on these definitions, we defined entrepreneurial innovations as "the generation of novel products, services, and technologies that emerged within an efficient interface among agents involved in entrepreneurial ecosystems and innovation ecosystems.…”
Section: Defining Entrepreneurial Innovationsmentioning
confidence: 99%